2006
DOI: 10.1007/s00134-006-0247-x
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of the medial lumen is a risk factor for catheter-related bloodstream infection

Abstract: Colonization of the medial lumen is an independent risk factor for triple-lumen catheter-related bloodstream infection, possibly due to the absence of use of this lumen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
0
0
3
Order By: Relevance
“…However, bacterial contamination of intravascular devices has been shown to be associated with increased morbidity in other health care settings. [32][33][34][35][36][37] These study results confirm that the previously reported problems of stopcock contamination, suboptimal hand hygiene, and suboptimal environmental decontamination are not limited to a single institution. [12][13][14] Thus, there is a universal need for improvement in intraoperative infection control.…”
Section: Discussionsupporting
confidence: 92%
“…However, bacterial contamination of intravascular devices has been shown to be associated with increased morbidity in other health care settings. [32][33][34][35][36][37] These study results confirm that the previously reported problems of stopcock contamination, suboptimal hand hygiene, and suboptimal environmental decontamination are not limited to a single institution. [12][13][14] Thus, there is a universal need for improvement in intraoperative infection control.…”
Section: Discussionsupporting
confidence: 92%
“…cateteres multi-lúmen são particularmente susceptíveis à colonização bacteriana, pois cada luz é uma fonte potencial de ICS, uma vez que são utilizados para diferentes fins ao mesmo tempo, como monitorização da pressão venosa central (PVC), amostragem arterial, administração de nutrição parenteral total (NPT) e administração contínua e/ou intermitente de medicamentos (44)(45) . Cabe lembrar que no caso do CVC triplo lúmen este tem maior diâmetro e necessidade de pequena incisão na pele para inserção, elevando ainda mais o risco para ICS (19,41) .…”
Section: Fatores De Risco Para Infecção Da Corrente Sanguínea Associaunclassified
“…[104][105][106][107][108] Σε Καυκάσιους, οι TLR2-, TLR4και TLR9-SNPs είναι οι πιο συχνές μεταλλάξεις των TLR με συχνότητα από 8% -28%. [109][110][111]191 [11][12][13][14][15][16][17][18][19][20]24 Αν και σε άλλες μελέτες έχει βρεθεί συσχέτιση των TLRs με την επίπτωση της βακτηριαιμίας από Gram(-) παθογόνα, 200,201,206,209 Gram(+) παθογόνα, 109,192,196,197 107,191,197,200,212,245,246 Ωστόσο, ο ρόλος των συγκεκριμένων TLR SNPs στην βαρύτητα και την εξέλιξη της σήψης εξακολουθεί να παραμένει εξαιρετικά αμφιλεγόμενη. 191,203 [108][109][110][111]191 Η διερεύνηση των πολυμορφισμών των TLRs και η σύνδεσή τους με την ευαισθησία των μολυσματικών λοιμώξεων από την ICU από άλλες πολυκεντρικές μελέτες με μεγάλο αριθμό περιλαμβανομένων ασθενών θεωρείται απαραίτητη.…”
Section: κριτήριοunclassified
“…συντελούν στην επιμονή της βακτηριαιμίας. καθετήρων,[11][12][13][14][15][16][17] η αιμοκάθαρση,18 η παρεντερική διατροφή,19,20 ο καθετηριασμός της ουροδόχου κύστης, 20 η χρήση σωλήνων και οι στομίες,21 η μηχανική υποστήριξη της αναπνοής,11 οι υποκείμενοι νόσοι όπως καρκίνος,22 ανοσοανεπάρκειες, 23 αυτοάνοσοι νόσοι, 24 ο σακχαρώδης διαβήτης, 25 η υποθρεψία, 26 η νεφρική και ηπατική ανεπάρκεια,24 οι μεταμοσχεύσεις,26 οι χειρουργικές επεμβάσεις στην περιοχή της κοιλιάς αλλά και του ουροποιογενετικού συστήματος,20,23,24 τα εγκαύματα, 21 η πρόσφατη λήψη αντιβιοτικών ευρέος φάσματος (κεφαλοσπορίνες τρίτης ή τέταρτης γενιάς, αζτρεονάμη, κινολόνες, πιπερακιλλίνη ταζομπακτάμη, καρπαπενέμες) 27. 1.7 Κλινική εικόναΗ κλινική εικόνα της βακτηριαιμίας ποικίλλει.…”
unclassified